Changes to virus taxonomy, the international code of virus classification and nomenclature, and the ICTV statutes ratified by the International Committee on Taxonomy of Viruses (2025) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Juliana Freitas-Astúa; R. Curtis Hendrickson; Holly R. Hughes; Mart Krupovic; et al. (Archives of Virology, 2026)
The 56th meeting of the Executive Committee (EC) of the International Committee on Taxonomy of Viruses (ICTV) was held in Bari, Italy, in July/August, 2024, and 115 submitted taxonomy proposals were reviewed. A total of 112 were subsequently ratified by the ICTV membership. An additional 9 error correction proposals were also approved in August 2025. This article lists the taxonomy proposals that have now been incorporated into release 40 version v2 of the Master Species List ( https://ictv.global/msl ), the Virus Metadata Resource ( https://ictv.global/vmr ), and associated ICTV databases. In addition to the assignments of 1,563 new virus species, 243genera, 55 families, 11 orders, and 8 classes, there were substantial additions to higher taxonomic ranks. These include the creation of a new realm ( Singelaviria ), which is based on the recognition of a separate evolutionary origin for the hallmark capsid genes of members of the kingdom Helvetiavirae. These express capsid proteins forming a single jelly-roll fold that is structurally and evolutionarily distinct from those of members of the family Bamfordvirae , assigned to the realm Varidnaviria . Furthermore, the realm Varidnaviria underwent a major reorganization, including the addition of a new kingdom, Abadenavirae . Another notable change was the classification of the vertebrate-infecting single-stranded DNA anellovirids into a new phylum Commensaviricota (kingdom Shotokuvirae , realm Monodnaviria ). Archaeal viruses infecting the hyperthermophilic Archaeoglobi were assigned to a new phylum Calorviricota , in the kingdom Trapavirae (realm Monodnaviria ), whereas RNA viruses infecting hyperthermophilic bacteria were classified into a new phylum Artimaviricota (realm Riboviria ). In recognition of his extensive and valuable contributions to virus taxonomic developments in Study Groups and over the period of his EC membership, Stuart Siddell was honoured as a new life member of the ICTV. The ICTV has created a new strategy for disseminating information on taxonomy advances through annual open-access publication of citeable taxonomy proposal summaries from each ICTV Subcommittee. A collective total of 354 co-authors of the seven summaries were drawn from members of each Subcommittee, the EC, and a very large number of contributors from the wider virology community.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Assessing the Reliability of a New One-Line Model for Predicting Shoreline Evolution with Impoundment Field Experiment Data - Antonio Francone; David J. Simmonds (Journal of Marine Science and Engineering, 2023)
The advancement of knowledge in the field of coastal morphodynamics is currently highly relevant, as it provides valuable insights into the complex and dynamic nature of coastal systems and helps coastal engineers and researchers to better understand and manage the risks associated with coastal hazards. Managing and protecting coastal areas requires accurate measurements and the availability of reliable numerical models for predicting shoreline evolution. The present study focuses on verifying the reliability of a recent one-line model: the General Shoreline beach (GSb) model. The numerical simulations were performed using wave data observed by the Acoustic Wave and Current profiler and the Channel Coast Observatory buoy. The numerical results were compared with high-resolution shoreline data collected from an ARGUS monitoring station during the impoundment experiment conducted in Milford-on-Sea, UK. The numerical results demonstrated that the GSb model accurately predicts shoreline evolution, particularly for mixed beaches. The findings of the present study also show the effectiveness of the GSb online numerical model in predicting day-to-day changes in shoreline dynamics caused by wave attack. The high-resolution dataset of the ARGUS observations combined with wave data collected during the field experiment could be valuable resources for coastal researchers to further evaluate and improve numerical models of coastal morphodynamics.

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

Differentiating between viruses and virus species by writing their names correctly - Francisco Murilo Zerbini; Stuart G. Siddell; Arcady R. Mushegian; Peter J. Walker; Elliot J. Lefkowitz; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Bas E. Dutilh; María Laura García; Sandra Junglen; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Prediction of Shoreline Evolution. Reliability of a General Model for the Mixed Beach Case - Giuseppe R. Tomasicchio; Antonio Francone; David J. Simmonds; Felice D’Alessandro; Ferdinando Frega (Journal of Marine Science and Engineering, 2020)
In the present paper, after a sensitivity analysis, the calibration and verification of a novel morphodynamic model have been conducted based on a high-quality field experiment data base. The morphodynamic model includes a general formula to predict longshore transport and associated coastal morphology over short- and long-term time scales. With respect to the majority of the existing one-line models, which address sandy coastline evolution, the proposed General Shoreline beach model (GSb) is suitable for estimation of shoreline change at a coastal mound made of non-cohesive sediment grains/units as sand, gravel, cobbles, shingle and rock. In order to verify the reliability of the GSb model, a comparison between observed and calculated shorelines in the presence of a temporary groyne deployed at a mixed beach has been performed. The results show that GSb gives a good agreement between observations and predictions, well reproducing the coastal evolution.

Design catalogue for eco-engineering of coastal artificial structures: a multifunctional approach for stakeholders and end-users - Kathryn A. O’Shaughnessy; Stephen J. Hawkins; Ally J. Evans; Mick E. Hanley; Paul Lunt; Richard C. Thompson; Robert A. Francis; Simon P. G. Hoggart; Pippa J. Moore; Gregorio Iglesias; David Simmonds; James Ducker; et al. (Urban Ecosystems, 2020)
Coastal urbanisation, energy extraction, food production, shipping and transportation have led to the global proliferation of artificial structures within the coastal and marine environments (sensu “ocean sprawl”), with subsequent loss of natural habitats and biodiversity. To mitigate and compensate impacts of ocean sprawl, the practice of eco-engineering of artificial structures has been developed over the past decade. Eco-engineering aims to create sustainable ecosystems that integrate human society with the natural environment for the benefit of both. The science of eco-engineering has grown markedly, yet synthesis of research into a user-friendly and practitioner-focused format is lacking. Feedback from stakeholders has repeatedly stated that a “photo user guide” or “manual” covering the range of eco-engineering options available for artificial structures would be beneficial. However, a detailed and structured “user guide” for eco-engineering in coastal and marine environments is not yet possible; therefore we present an accessible review and catalogue of trialled eco-engineering options and a summary of guidance for a range of different structures tailored for stakeholders and end-users as the first step towards a structured manual. This work can thus serve as a potential template for future eco-engineering guides. Here we provide suggestions for potential eco-engineering designs to enhance biodiversity and ecosystem functioning and services of coastal artificial structures with the following structures covered: (1) rock revetment, breakwaters and groynes composed of armour stones or concrete units; (2) vertical and sloping seawalls; (3) over-water structures (i.e., piers) and associated support structures; and (4) tidal river walls.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Photooxidation of Nimbin and Salannin, Tetranortriterpenoids from the Neem Tree (Azadirachta indica) - Andrew P. Jarvis; Shaun Johnson; E. David Morgan; Monique S. J. Simmonds; Wally M. Blaney (Journal of Chemical Ecology, 1997)

SUB-GRID-SCALE TOPOGRAPHY AND THE SIMULATION OF NORTHERN HEMISPHERE SNOW COVER - DAVID J. WALLAND; IAN SIMMONDS (International Journal of Climatology, 1996)